Moving toward consensus: an examination of trends in investment fair values - Hogan, Chris E.; Stein, Sarah E.; Stuber, Sarah B. (Review of Accounting Studies, 2025)
Abstract A primary argument against fair value measurement is the lack of verifiability, where verifiability is defined as consensus in measurement by independent parties. We evaluate this argument by investigating trends in the consensus of reported fair values. Our findings indicate that consensus increased between 2005 and 2019, as evidenced by reductions in the fair value range and standard deviation. Further analyses suggest that enhanced data availability—driven by public dissemination of trade information—serves as a mechanism for this trend. We also document that securities subject to testing by larger external auditors with more resources to take advantage of enhanced data availability are associated with a stronger trend in increasing consensus. Finally, this trend appears to be stronger in situations when management has a heightened opportunity to record a biased estimate. While conventional arguments express concern over management’s ability to manipulate fair values, our results demonstrate patterns consistent with improved verifiability.